The Effect Of Leadership And Work Motivation On Teachers' Work Ethos In Junior High School State Kualuh Downstream District - Maidiana Maidiana; Khairuddin Khairuddin (LPPPIPublishing, 2022)
Study this aim for study The Effect Of Leadership and Work Motivation On Teachers Work Ethos In Junior High School State Kualuh Downstream District. Study this based on because problem influencing factors teacher work ethic. Method study conducted with use approach quantitative. M method data collection is a technique or how to do for collect data. Method pointing something method so that could show us through study library and research related fields with observation, and questionnaire or questionnaire. Data analysis technique conducted with analysis regression Double, Significant Test (t), Simultaneous Test (Ftest), and Coefficient Determination (R Test). Research Results show that the Influence Among Leadership school principals against ethos work Teacher State Junior High School in the District of Kualuh Hilir. This thing can be proven from the results of SPSS 21 data processing which is obtained from the results of hypothesis testing that shows that sign < and analysis tcount = 4,028 while score t table = 1.68288 means score t count > score t table. Influence Among motivation teacher work on ethos Teacher's work State Junior High School in the District of Kualuh Hilir. This thing can be proven from the results of SPSS 21 data processing which is obtained from the results of hypothesis testing that show that sign < and analysis tcount = 7.412 whereas score t table = 1.68288. Influence Among leadership and motivation teacher work on ethos Teacher's work Simultaneously, all public junior high schools in the Kualuh Hilir sub-district. This thing can be proven from the results of SPSS 21 data processing which is obtained the results of hypothesis testing that show that sign value < and Fcount 28,547 > F table 3,226, which means leadership and work motivation have a significant influence on the ethos of teacher work in SMP Negeri Se - Kualuh Hilir District, In Thing this the effect of 0.594, or have influence as big as 59,4.